Inversion-based propofol dosing for intravenous induction of hypnosis - Padula, Fabrizio; Ionescu, C.; Latronico, N.; Paltenghi, M.; Visioli, A.; Vivacqua, G. (Elsevier, 2016)
© 2016 Elsevier B.V.In this paper we propose an inversion-based methodology for the computation of a feedforward action for the propofol intravenous administration during the induction of hypnosis in general anesthesia. In particular, the typical initial bolus is substituted with a command signal that is obtained by predefining a desired output and by applying an input-output inversion procedure. The robustness of the method has been tested by considering a set of patients with different model parameters, which is representative of a large population.